2015
DOI: 10.1124/mol.114.096420
|View full text |Cite
|
Sign up to set email alerts
|

Chloride is an Agonist of Group II and III Metabotropic Glutamate Receptors

Abstract: The elemental anion chloride is generally considered a passive participant in neuronal excitability, and has never been shown to function as an agonist in its own right. We show that the antagonistmediated, glutamate-independent inverse agonism of group II and III metabotropic glutamate (mGlu) receptors results from inhibition of chloride-mediated activation. In silico molecular modeling, sitedirected mutagenesis, and functional assays demonstrate (1) that chloride is an agonist of mGlu3, mGlu4, mGlu6, and mGl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
2
8
1
Order By: Relevance
“…Previously, both Ca 2+ and Clions were proposed to display agonist activity on the mGlu3 receptor (DiRaddo et al, 2015;Vafabakhsh et al, 2015). However, in our experiments, Clper se does not display direct agonism, as revealed by the glutamate insensitive mGlu3 mutant T174A, which is not activated by Cl -.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Previously, both Ca 2+ and Clions were proposed to display agonist activity on the mGlu3 receptor (DiRaddo et al, 2015;Vafabakhsh et al, 2015). However, in our experiments, Clper se does not display direct agonism, as revealed by the glutamate insensitive mGlu3 mutant T174A, which is not activated by Cl -.…”
Section: Discussioncontrasting
confidence: 64%
“…Among them, two sites correspond to functional Clbinding sites that have been described in the VFT of most mGluRs, contrary to the mGlu2 receptor, which possesses only one of these functional sites (Tora et al, 2015). The first Clsite (Site 1) is located within VFT lobe 1, in a binding pocket adjacent to the glutamate binding site, which was previously predicted (Acher et al, 2011) and demonstrated to be a Clbinding site conserved in all mGluRs (Supplemental Fig.6A) (DiRaddo et al, 2015;Tora et al, 2015). The second site (Site 2) is created by the interface of both VFT lobes, when the receptor is in a closed active conformation and shows more divergence within the mGluR family.…”
Section: A Unique "Chloride Lock" Stabilizes the Active State Of The mentioning
confidence: 85%
See 1 more Smart Citation
“…1J). This is consistent with a recent study demonstrating that Clbinding to the ECD causes high basal activity of mGluR3 (24,25). Thus, the inverse agonist-induced increase and agonist-induced decrease of D Av in Fig.…”
Section: Relationship Among Average Diffusion Coefficient Ligand Binsupporting
confidence: 93%
“…The chloride ion has been shown to act as an agonist of group II and III mGlu receptors, and in particular it is an agonist of mGlu 3 but not mGlu 2 [97]. Mutagenesis and modeling showed the ion to bind in a cavity near the orthosteric binding site in the VFT domain.…”
Section: Group II Mglu Receptorsmentioning
confidence: 99%